2012
DOI: 10.1126/science.1214433
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Livestock Grazing Promotes Locust Outbreaks by Lowering Plant Nitrogen Content

Abstract: Current paradigms generally assume that increased plant nitrogen (N) should enhance herbivore performance by relieving protein limitation, increasing herbivorous insect populations. We show, in contrast to this scenario, that host plant N enrichment and high-protein artificial diets decreased the size and viability of Oedaleus asiaticus, a dominant locust of north Asian grasslands. This locust preferred plants with low N content and artificial diets with low protein and high carbohydrate content. Plant N conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
187
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(219 citation statements)
references
References 28 publications
(17 reference statements)
16
187
0
2
Order By: Relevance
“…An earlier study reported decreased survival and growth when M. bivittatus nymphs were fed P-fertilized wheat (1.86%P) (Smith, 1960) and suggested that, perhaps counter-intuitively, P fertilizer could be a way to improve wheat crops and decrease pests. These results fit with a growing body of literature showing cases in nature where herbivores may not be N or P limited and that high levels of these nutrients can decrease growth and survival (Boersma and Elser, 2006;Cease et al, 2012;Simpson and Raubenheimer, 2012). On the lower end of the P diets, Smith (1960) reported that the low-P wheat (0.17%P) decreased survival relative to control wheat.…”
Section: Effects Of Dietary P On Growth Development and Survivalsupporting
confidence: 79%
“…An earlier study reported decreased survival and growth when M. bivittatus nymphs were fed P-fertilized wheat (1.86%P) (Smith, 1960) and suggested that, perhaps counter-intuitively, P fertilizer could be a way to improve wheat crops and decrease pests. These results fit with a growing body of literature showing cases in nature where herbivores may not be N or P limited and that high levels of these nutrients can decrease growth and survival (Boersma and Elser, 2006;Cease et al, 2012;Simpson and Raubenheimer, 2012). On the lower end of the P diets, Smith (1960) reported that the low-P wheat (0.17%P) decreased survival relative to control wheat.…”
Section: Effects Of Dietary P On Growth Development and Survivalsupporting
confidence: 79%
“…Conflicting evidence is provided in Holmes et al (1979) who stated that some grasshopper species were more abundant in heavily grazed fields when compared with lightly grazed fields, while other species exhibited the opposite preference for infrequently grazed pastures with tall and dense vegetation. Cease et al (2012) also demonstrated that abundance of the locust Oedaleus asiaticus was promoted by heavy grazing in north Asian steppe grasslands by the lowering of plant nitrogen (N).…”
Section: The Effect Of Grazingmentioning
confidence: 99%
“…Vegetation has a key influence on grasshopper populations (Kang et al, 2007), and the degradation of grasslands can cause outbreaks of some locust species in the Eurasian steppe system (Cease et al, 2012). Agricultural activities may be responsible for an increase in the density of grasshoppers in Europe (Badenhausser & Cordeau, 2012).…”
Section: Discussionmentioning
confidence: 99%